2013
DOI: 10.1007/s00248-013-0245-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis Signature of Fecal Microbiota in Colorectal Cancer Patients

Abstract: The human gut microbiota is a complex system that is essential to the health of the host. Increasing evidence suggests that the gut microbiota may play an important role in the pathogenesis of colorectal cancer (CRC). In this study, we used pyrosequencing of the 16S rRNA gene V3 region to characterize the fecal microbiota of 19 patients with CRC and 20 healthy control subjects. The results revealed striking differences in fecal microbial population patterns between these two groups. Partial least-squares discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
301
5
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(356 citation statements)
references
References 40 publications
23
301
5
8
Order By: Relevance
“…Of potential relevance in this context, we also found Fn load in the stool of CRC patients to be significantly higher than that of adenoma patients (p=0.0316) and also healthy control patients (p=0.0201), although we had a small number of stool samples from CRC patients available for analysis. Interestingly, a recent Chinese study examining faecal microbial communities in healthy and CRC groups observed a marked increase in the relative abundance of Fn in the CRC cancer cohort compared with the healthy control group [35].…”
Section: Discussionmentioning
confidence: 96%
“…Of potential relevance in this context, we also found Fn load in the stool of CRC patients to be significantly higher than that of adenoma patients (p=0.0316) and also healthy control patients (p=0.0201), although we had a small number of stool samples from CRC patients available for analysis. Interestingly, a recent Chinese study examining faecal microbial communities in healthy and CRC groups observed a marked increase in the relative abundance of Fn in the CRC cancer cohort compared with the healthy control group [35].…”
Section: Discussionmentioning
confidence: 96%
“…To detect significant differences in microbial abundances among treatments and growth conditions, ANOVA was applied using Tukey's test (␣ ϭ 0.05) (58,59). Spearman's rank correlations (P Ͻ 0.01) (60,61) were used to compare relative microbial abundances with the efficacy against downy mildew on leaf discs and with the environmental parameters of rainfall (mm), maximum, minimum, and mean temperatures (°C) at each location.…”
Section: Methodsmentioning
confidence: 99%
“…are enriched in CRC tissues relative to adjacent healthy tissues (Castellarin et al, 2012). For example, a Chinese study that analysed faecal microbial communities in healthy individuals and CRC patients identified a remarkable increase in Fusobacterium nucleatum counts in the CRC cohort compared with the healthy control group (Wu et al, 2013). Similarly, a North American study found that F. nucleatum was more abundant in stool samples from patients with CRC than in those from healthy subjects (Kostic et al, 2012(Kostic et al, , 2013.…”
Section: Introductionmentioning
confidence: 97%
“…Increasing evidence suggests that gut microbiota play an important role in the development of CRC (Wu et al, 2013). Fusobacterium spp., in particular, have been associated with human CRC, as confirmed by metagenomic analyses using whole-genome (Kostic et al, 2012), transcriptome (Kostic et al, 2012(Kostic et al, , 2013 and bacterial 16S ribosomal RNA sequencing (Marchesi et al, 2011;Kostic et al, 2012).…”
Section: Introductionmentioning
confidence: 99%